A DESCRIPTIVE ANALYSIS OF SLANG TERMS IN SCARFACE MOVIE - Carlos, Martin; Gailea, Nurhaeda; Rima, Rosmania (Fakultas Komunikasi, Sastra, dan Bahasa, 2019)
The present research analyses the use of slang terms in Scarface movie. The present research aims to examine types of slang, word formation as well as the meaning of slang words used in the movie. The present research uses a descriptive qualitative method to classify and analyze the slang utterances based on Yule?s theory of word formation. The results show that the movie contains forty seven slang words such as ain?t, shit, and gotta. Secondly, the results show following word formations: eight borrowing, five blending, four clipping, one multiple process, six compounding and one back formation. Lastly, the results describe the literal and figurative meanings of the slang words according to NTC?s Dictionary of American Slang and Colloquial.